Differences in the Meaning of Written and Spoken Language Phonemes - Siregar, Ayunda Putri Amira; Surayya , Azizah; Lubis , Yani (Jurnal Pendidikan Rafflesia, 2023)
Currently, the digital world has become a part of Indonesian people's daily lives, especially sending someone a message means that people use the phone, WhatsApp, Instagram, courier and more. . However, with the increased ease of use, we still often see people struggling with the spoken language. The goal of our research is to find out the difference between written and spoken language by the method we use so that we can reach the discussion and find out which language is better to use in Indonesian.